Oxidative stress in testicular tissues of rats exposed to cigarette smoke and protective effects of CAPE - Ozyurt, Huseyin; Pekmez, Hidir; Parlaktas, Suha; Kus, Ilter; Ozyurt, Birsen; Sahin, Semsettin; Sarsilmaz, Mustafa (Blackwell Publishing, 2006)
[Abstract Not Available]
31st Congress of the Federation-of-European-Biochemical-Societies (FEBS) -- JUN 24-29, 2006 -- Istanbul, TURKEY